HUBUNGAN ANTARA DAERAH TEMPAT TINGGAL DENGAN KEJADIAN DIARE PADA BALITA USIA 24-59 BULAN DI SUMATERA UTARA - Hengki Frengki Manullang; Fithri Handayani Lubis; Syafrina Ulfah; Monika Nina Ginting (Jurnal Penelitian Kesmasy, 2025)
Diarrhea is an endemic disease of significant concern in Indonesia and ranks as the second-largest cause of mortality among children under the age of five. This study aims to identify the correlation between residential location and the incidence of diarrhea in toddlers aged 24–59 months in North Sumatra Province, utilizing data from the 2023 Indonesian Health Survey (SKI). This research used a quantitative design with a cross-sectional approach and included 3784 toddlers aged 24 to 59 months. Analysis was performed using the chi-square test. The results of the analysis showed a p-value of 0,002 (p < 0,05), indicating a strong correlation between place of residency and the incidence of diarrhea. An odds ratio (OR) of 1,670 indicates that toddlers living in urban areas are 1,670 times more predisposed to experiencing diarrhea compared to their rural counterparts. The findings underscore the necessity of considering regional context in the fight against diarrhea in North Sumatera, necessitating interventions adapted to urban and rural settings to enhance the specificity and efficacy of prevention programs aimed at lowering diarrhea incidence in toddlers.